Virtual Demons: Blue Whale and Moral Panic in the Digital Age - Karaosmanoglu, Kerem (WILEY, 2026)
This article examines the Blue Whale phenomenon as a case of moral panic with particular attention to its trajectory in Turkey. Originating in Russia in 2015, Blue Whale spread rapidly through sensationalist media coverage and soon became framed as a global threat to adolescents. In Turkey, the panic intensified between 2016 and 2019, marked by repetitive headlines, expert warnings, state interventions, and even academic publications, all of which reinforced a protectionist discourse while leaving the veracity of the phenomenon largely unquestioned. Adopting a sociological perspective, this article situates Blue Whale within the broader tradition of moral panic studies, highlighting how archetypes of evil and conspiratorial imagination shaped its circulation. It further argues that the Turkish experience mirrors global patterns yet unfolded through its own media ecologies and cultural anxieties. Ultimately, the Blue Whale panic reveals how digital-age fears are constructed, sustained, and localized in specific social contexts.
Keywords: Anthropology; History; Sociology